THE IMPORTANCE OF LOCUS OF CONTROL, ORGANIZATIONAL CULTURE, AND WORK STRESS IN AFFECTING THE EMPLOYEE PERFORMANCE AT PT SANKEIKID MANUTEC INDONESIA - Alvianti, Risma; Hawignyo, Hawignyo (Dinasti International Journal of Digital Business Management, 2021)
This research aims to discover the affect caused by locus of control, organization culture and work stress to employee performance at PT Sankeikid Manutec Indonesia. The advancing in the globalization era has become a gateway and makes it easier for companies to develop their expansion to various countries, this surely brings positive and negative impacts, so that companies will survive, companies should be able to maintain and develop their employees to the maximum. The method used in this research was descriptive verification with quantitative approach. The research sample was the employees of PT Sankeikid Manutec Indonesia with total 165 respondents. The research outcomes were locus of control and organizational culture which have an impact on employee performance, while work stress has no affect to it. Locus of control, organizational culture and work stress simultaneously affect to employee performance.